Essentials computing for business: Microsoft Office 2010 - Ismail, Shahifol Arbi; Mohd Nasir, Mohd Herry; Mat Saat, Rafeah; Yaakub, Nor Asiah (Universiti Utara Malaysia Press, 2016)
Essentials Computing for Business: Microsoft Office 2010 introduces basic computing technologies to accounting students and professionals who will find it relevant and useful.This book:·Helps you understand the actual theoretical and practical importance and relevance of Information Technology to the business community, particularly accounting practitioners.Helps you acquire basic to advanced skills for operating office productivityprogrammess,including word processing, presentation, spreadsheet and database.Gives you a step-by-step understanding of how to complete a task by using well crafted “hands-on” project samples.Enhances your skills and abilities to operate an accounting programme by comparing the samples provided in the book to your own completed projects.Provides additional exercises at the end of each chapter to further enhance your understanding.